Content Based Video Retrieval Intelligent Security System - Karnila, Sri; Irianto, Suhendro Yusuf; Kurniawan, Rio (Prosiding International conference on Information Technology and Business (ICITB), 2018)
In this work we try to explore the use of content based video retrieval method to build an application in detecting moving object. The application will detect and recognize human walking styleeness in intelligent security system. Recently, the growth of crime activities in our neighbors going very fast. Further more text or characters security system by using password has some disadvantages such as easily to fraud , duplicate, and hard to remember as many passwords or PIN have to remember today. In order to solve to situation, intelligent security system urgently needed to protect our property and life. It needed to work 24 hours a day 7 days a week and 12 monthhs a year without tiring and exhausting. In this work we use content based video retrieval or CBVR in building the application. Approximately 500 video clips of human walking style used in this research, it has 30 second to 60 seconds in each clip. We use a moving glass doors to test and simulate the application, when a walking style detect and recognize .The simulation and testing show that application built from this research is quite good in detecting and recognizing one’s walking style, even though its accuracy and the effectiveness has not been calculated yet.Keywords : Video retrieval, intelligent security, walking styleness